2022
DOI: 10.1016/j.thromres.2021.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Pre-administration of a carboxypeptidase inhibitor enhances tPA-induced thrombolysis in mouse microthrombi: Evidence from intravital imaging analysis

Abstract: Introduction: Thrombolysis using recombinant tissue-type plasminogen activator (rt-PA) is the pharmacological treatment of choice in acute thrombotic events. However, a narrow therapeutic window and bleeding complications limit its use. We describe the role of carboxypeptidase inhibitor from potato tuber (PTCI), an inhibitor of activated thrombin-activatable fibrinolysis inhibitor (TAFIa), on Glu-plasminogen accumulation and microthrombus dynamics in vivo and demonstrate its influence on rt-PA-mediated thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…40 The border of the vascular injury site surrounded by normal vascular endothelial cells could be the candidate place where both thrombin activity and TM are expected to exist at sufficient amounts to efficiently activate TAFI. Further analysis to determine the spatiotemporal regulation of TAFI activation on TM-expressing vascular endothelial cells, as well as in vivo real-time imaging techniques performed by our group [43][44][45] and others, [46][47][48] seems to contribute to the understanding of when and where to activate TAFI and protein C.…”
Section: Discussionmentioning
confidence: 99%
“…40 The border of the vascular injury site surrounded by normal vascular endothelial cells could be the candidate place where both thrombin activity and TM are expected to exist at sufficient amounts to efficiently activate TAFI. Further analysis to determine the spatiotemporal regulation of TAFI activation on TM-expressing vascular endothelial cells, as well as in vivo real-time imaging techniques performed by our group [43][44][45] and others, [46][47][48] seems to contribute to the understanding of when and where to activate TAFI and protein C.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Mathews et al. [ 159 ] showed that CPI, a natural carboxypeptidase inhibitor, accelerated rt-PA–mediated thrombolysis in mice, when given prior to thrombolytic therapy initiation.…”
Section: Isth Congress Reportmentioning
confidence: 99%